Preface -4 - Kahraman, Cengiz; Cebi, Selcuk; Oztaysi, Basar; Onar, Sezi Cevik; Tolga, Cagrı; Sari, Irem Ucal; Otay, Irem (Springer Science and Business Media Deutschland GmbH, 2025)
[Abstract Not Available]
7th International Conference on Intelligent and Fuzzy Systems, INFUS 2025 -- 29 July 2025 through 31 July 2025 -- Istanbul -- 336089
Keywords: [Keywords Not Available]